Hiellen Pole - A. de Menil (1968)
This replica of a Haida pole was carved by a Tsimshian Chief named William Jeffey. The original pole once stood in the village of Hiellen, Haida Gwaii. The original pole was commissioned by A.E. Edenshaw.